The impact of introducing multidisciplinary care assessments on access to rheumatology care in British Columbia: an interrupted time series analysis - Ross Duncan; Lucy Cheng; Michael R. Law; Kam Shojania; Mary A. De Vera; Mark Harrison (BMC, 2022)
Abstract Background In 2011 the British Columbia (BC) Ministry of Health introduced a new fee-for-service billing code that allowed "Multidisciplinary Care Assessment" (MCA). This change has the potential to change access to and quality of care for patients. This study aimed to explore the impact on access to rheumatology services in the province. Methods Fee-for-service rheumatology billings were evaluated for each rheumatologist 2 years before and after use of the MCA code. Numbers of 1) unique patients and 2) services provided per month were used as proxy measures of access to care. A multiple-baseline interrupted time series model assessed the impact of the MCA on levels and trends of the access outcomes. Results Our analysis consisted of 82,360 patients cared for by 26 rheumatologists who billed for an MCA. In our primary analysis we observed a sustained increase in the mean number of unique patients of 4.9% (95% CI: 0.0% to 9.9%, p = 0.049) and the mean number of services of 7.1% (95% CI: 1.0% to 13.6%, (p = 0.021), per month provided by a rheumatologist, corresponding to the initial use of MCA. Conclusion The introduction of the MCA code was associated with an initial increase in the measures of access, which was maintained but did not increase over time. Our study suggests that the use of Multidisciplinary Care Assessment can contribute to expanding and/or sustaining access to care for people with complex chronic conditions, like rheumatic diseases.